Optical emission spectroscopy of low temperature PECVD of diamond and DLC films - Patacsil, Crismar P. (c2004.)
"The gas phase chemistry in low temperature (<300°C) diamond and diamond-like carbon (DLC) chemical vapor deposition processes was investigated using optical emission spectroscopy (OES) to determine the effects of the different deposition parameters such as methane concentration, substrate temperature, plasma current and gas pressure in relation to diamond growth on silicon substrate. The OES data were analyzed and correlated to significant factors favorable for diamond deposition such as the ,eam electron temperature, Tₑ, and the relative concentration levels of methane radicals (CH and CH⁺). The results indicate that the optimum deposition parameters for the low temperature diamond CVD system could be achieve by applying low methane concentration (1% to 3% methane in hydrogen), high substrate temperature (above 275°C), low pressure (<20 mTorr) and high plasma current (above 30mA). Diamond films were attempted to be deposited on silicon substrate while gathering the OES data using varying methane concentrations (1%, 3%, 5% and 8% methane in hydrogen) at fixed pressure (10 mTorr) and fixed plasma current (50 mA). X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) characterization of the depositied samples confirmed that diamond films were deposited at low methane concentrations (1% to 3%). Samples deposited using 5% methane resulted in DLC films while 8% methane concentration yielded graphitic carbon deposits. Film samples were also deposited using varying substrate temperature (175°C - 300°C). Samples deposited at substrate temperature above 200°C yielded diamond characteristics while films deposited at lower substrate temperatures resulted in DLC deposits."
"May 2004."
Thesis (M.S. Physics)--University of the Philippines Diliman.
Keywords: Emission spectroscopy; Diamond crystals; Plasma-enhanced chemical vapor deposition